At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the integral of the expression [tex]\( x^5 \sqrt{x^3 + 9} \, dx \)[/tex], we need to proceed methodically. Here is a detailed step-by-step solution:
1. Simplify the Integrand:
We'll first rewrite the integrand [tex]\( x^5 \sqrt{x^3 + 9} \)[/tex] for better clarity.
[tex]\[ x^5 \sqrt{x^3 + 9} \][/tex]
2. Substitute to Simplify:
Let's consider a substitution [tex]\( u = x^3 + 9 \)[/tex]. Therefore, [tex]\( \frac{du}{dx} = 3x^2 \)[/tex] or [tex]\( du = 3x^2 \, dx \)[/tex]. Solving for [tex]\( dx \)[/tex], we get:
[tex]\[ dx = \frac{du}{3x^2} \][/tex]
3. Express [tex]\( x \)[/tex] in Terms of [tex]\( u \)[/tex]:
From [tex]\( u = x^3 + 9 \)[/tex], we have [tex]\( x^3 = u - 9 \)[/tex]. Hence,
[tex]\[ x^6 = (x^3)^2 = (u - 9)^2 \][/tex]
4. Rewrite the Integral:
Substitute [tex]\( u \)[/tex] and [tex]\( dx \)[/tex] into the integral:
[tex]\[ \int x^5 \sqrt{x^3 + 9} \, dx = \int x^5 \sqrt{u} \cdot \frac{du}{3x^2} \][/tex]
Simplify the integrand:
[tex]\[ \int x^5 \sqrt{u} \cdot \frac{du}{3x^2} = \int \frac{x^5 \sqrt{u}}{3x^2} \, du = \int \frac{x^3 x^2 \sqrt{u}}{3x^2} \, du = \int \frac{x^3 \sqrt{u}}{3} \, du \][/tex]
As [tex]\( x^3 = u - 9 \)[/tex], the integrand becomes:
[tex]\[ \int \frac{(u - 9) \sqrt{u}}{3} \, du \][/tex]
5. Distribute and Simplify:
Distribute [tex]\( \sqrt{u} \)[/tex] and split the integral:
[tex]\[ \int \frac{(u - 9) \sqrt{u}}{3} \, du = \int \frac{u^{3/2} - 9u^{1/2}}{3} \, du = \frac{1}{3} \int (u^{3/2} - 9u^{1/2}) \, du \][/tex]
Separate the integrals:
[tex]\[ \frac{1}{3} \left( \int u^{3/2} \, du - 9 \int u^{1/2} \, du \right) \][/tex]
6. Evaluate the Integrals:
Integrate each term separately:
[tex]\[ \int u^{3/2} \, du = \frac{2}{5} u^{5/2} \][/tex]
[tex]\[ \int u^{1/2} \, du = \frac{2}{3} u^{3/2} \][/tex]
Substitute back:
[tex]\[ \frac{1}{3} \left( \frac{2}{5} u^{5/2} - 9 \cdot \frac{2}{3} u^{3/2} \right) \][/tex]
Simplify:
[tex]\[ \frac{1}{3} \left( \frac{2}{5} u^{5/2} - 6 u^{3/2} \right) \][/tex]
[tex]\[ \frac{1}{3} \cdot \frac{2}{5} u^{5/2} - \frac{1}{3} \cdot 6 u^{3/2} = \frac{2}{15} u^{5/2} - 2 u^{3/2} \][/tex]
7. Substitute [tex]\( u \)[/tex] Back to [tex]\( x \)[/tex]:
Recall [tex]\( u = x^3 + 9 \)[/tex]:
[tex]\[ \frac{2}{15} (x^3 + 9)^{5/2} - 2 (x^3 + 9)^{3/2} \][/tex]
Putting everything together, the integral is:
[tex]\[ \int x^5 \sqrt{x^3 + 9} \, dx = \frac{2}{15} x^6 \sqrt{x^3 + 9} + \frac{2}{5} x^3 \sqrt{x^3 + 9} - \frac{36}{5} \sqrt{x^3 + 9} + C \][/tex]
Where [tex]\( C \)[/tex] is the constant of integration.
1. Simplify the Integrand:
We'll first rewrite the integrand [tex]\( x^5 \sqrt{x^3 + 9} \)[/tex] for better clarity.
[tex]\[ x^5 \sqrt{x^3 + 9} \][/tex]
2. Substitute to Simplify:
Let's consider a substitution [tex]\( u = x^3 + 9 \)[/tex]. Therefore, [tex]\( \frac{du}{dx} = 3x^2 \)[/tex] or [tex]\( du = 3x^2 \, dx \)[/tex]. Solving for [tex]\( dx \)[/tex], we get:
[tex]\[ dx = \frac{du}{3x^2} \][/tex]
3. Express [tex]\( x \)[/tex] in Terms of [tex]\( u \)[/tex]:
From [tex]\( u = x^3 + 9 \)[/tex], we have [tex]\( x^3 = u - 9 \)[/tex]. Hence,
[tex]\[ x^6 = (x^3)^2 = (u - 9)^2 \][/tex]
4. Rewrite the Integral:
Substitute [tex]\( u \)[/tex] and [tex]\( dx \)[/tex] into the integral:
[tex]\[ \int x^5 \sqrt{x^3 + 9} \, dx = \int x^5 \sqrt{u} \cdot \frac{du}{3x^2} \][/tex]
Simplify the integrand:
[tex]\[ \int x^5 \sqrt{u} \cdot \frac{du}{3x^2} = \int \frac{x^5 \sqrt{u}}{3x^2} \, du = \int \frac{x^3 x^2 \sqrt{u}}{3x^2} \, du = \int \frac{x^3 \sqrt{u}}{3} \, du \][/tex]
As [tex]\( x^3 = u - 9 \)[/tex], the integrand becomes:
[tex]\[ \int \frac{(u - 9) \sqrt{u}}{3} \, du \][/tex]
5. Distribute and Simplify:
Distribute [tex]\( \sqrt{u} \)[/tex] and split the integral:
[tex]\[ \int \frac{(u - 9) \sqrt{u}}{3} \, du = \int \frac{u^{3/2} - 9u^{1/2}}{3} \, du = \frac{1}{3} \int (u^{3/2} - 9u^{1/2}) \, du \][/tex]
Separate the integrals:
[tex]\[ \frac{1}{3} \left( \int u^{3/2} \, du - 9 \int u^{1/2} \, du \right) \][/tex]
6. Evaluate the Integrals:
Integrate each term separately:
[tex]\[ \int u^{3/2} \, du = \frac{2}{5} u^{5/2} \][/tex]
[tex]\[ \int u^{1/2} \, du = \frac{2}{3} u^{3/2} \][/tex]
Substitute back:
[tex]\[ \frac{1}{3} \left( \frac{2}{5} u^{5/2} - 9 \cdot \frac{2}{3} u^{3/2} \right) \][/tex]
Simplify:
[tex]\[ \frac{1}{3} \left( \frac{2}{5} u^{5/2} - 6 u^{3/2} \right) \][/tex]
[tex]\[ \frac{1}{3} \cdot \frac{2}{5} u^{5/2} - \frac{1}{3} \cdot 6 u^{3/2} = \frac{2}{15} u^{5/2} - 2 u^{3/2} \][/tex]
7. Substitute [tex]\( u \)[/tex] Back to [tex]\( x \)[/tex]:
Recall [tex]\( u = x^3 + 9 \)[/tex]:
[tex]\[ \frac{2}{15} (x^3 + 9)^{5/2} - 2 (x^3 + 9)^{3/2} \][/tex]
Putting everything together, the integral is:
[tex]\[ \int x^5 \sqrt{x^3 + 9} \, dx = \frac{2}{15} x^6 \sqrt{x^3 + 9} + \frac{2}{5} x^3 \sqrt{x^3 + 9} - \frac{36}{5} \sqrt{x^3 + 9} + C \][/tex]
Where [tex]\( C \)[/tex] is the constant of integration.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.